2019
DOI: 10.20886/ijfr.2019.6.1.69-83
|View full text |Cite
|
Sign up to set email alerts
|

STUDY ON PRIMING METHODS TO ENHANCE THE VIABILITY AND VIGOR OF TREMA (Trema orientalis LINN. BLUME) SEEDS

Abstract: STUDY ON PRIMING METHODS TO ENHANCE THE VIABILITY AND VIGOR OF TREMA (Trema orientalis Linn. Blume) SEEDS. Trema is one of tropical forest trees that have many advantages such as wood for construction, pulp and charcoal, leaves for medicine and bark for dye material. One constrain of the development of this species is the difficulties of the germination of the seeds and rapid seed deterioration after storing. Therefore, there should be found a method to solve the problem. This paper determines the proper metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Yet only a small fraction may germinate under favourable conditions due to the dormant nature of the seeds [ 95 , 96 ]. Though several species of birds aid in the seed dispersal of T. orientale , fleshly ripe fruits rarely germinate and mostly decay especially in storage [ [97] , [98] , [99] ]. Hence, requiring intervention to preserve and accelerate its germination process.…”
Section: Domestication Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet only a small fraction may germinate under favourable conditions due to the dormant nature of the seeds [ 95 , 96 ]. Though several species of birds aid in the seed dispersal of T. orientale , fleshly ripe fruits rarely germinate and mostly decay especially in storage [ [97] , [98] , [99] ]. Hence, requiring intervention to preserve and accelerate its germination process.…”
Section: Domestication Potentialmentioning
confidence: 99%
“…A recent study by Nugraheni and Yuniarti [ 100 ], recommended that the optimum condition to maintain seed viability for at least one month and speed germination of T. orientale is to dry it for 24 hr, and put it in an air-tight aluminium foil container in an air condition room. Similarly, the highest growth uniformity of 74.75 % and 72 % before storage and after storage respectively was obtained by subjecting T. orientale seeds to a hydrated-dehydrated procedure [ 99 ]. Studies by Rodrigues and Rodrigues [ 101 ], indicated the potential of enhancing the seeds of T .…”
Section: Domestication Potentialmentioning
confidence: 99%
“…In another research, seeds of Trema orientalis Linn. Blume benefited from a hydration-dehydration process, regardless of whether it were applied before or after storage (Yuniarti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%